Atraksi Bestari: set permainan pembelajaran Bahasa Melayu - Mohd Noor, Muhammad Nazirul; Salman, Ainnul Jannah; Iszam Kamal, Isha Farzana; Abd Kamal, Muhammad Hafiz Zhafri; Mohd Borhan, Ibrahim (Politeknik Metro Johor Bahru, 2024)
Education will always be the primary concern. The United Nations (UN) placed Education on Sustainable Development Goal 4 to allow everyone to acquire knowledge, skills, and values for a better future. However, when the COVID-19 pandemic hit the world, our education system lost control and significantly impacted the students and educators. Teaching and learning after the post-covid is challenging for teachers and students in Malaysia. Gamification is one of the teaching methods that build students' interest in learning. Gamification learning aims to enhance students' motivation to learn, interact with others, compete, and accomplish objectives. Therefore, Atraksi Bestari is a set of games that focuses on boosting students' learning motivation and helping students learn Bahasa Melayu in a fun and cheerful environment. Atraksi Bestari consists of 2 types of games: Rotasi and Wizard School. This product is mainly used for Standard 5 and 6 students in SK Panchor, Muar Johor. This set of games has significantly aided students in studying the Malay language. It impacts not only the students but also the teachers, giving them a space to provide more meaningful and impactful teaching and learning experiences.